(untitled) (Indonesian Art and Justice Review, 2025)
As Indonesia faces the dual pressures of globalization and rapid urbanization, the country’s indigenous art forms are increasingly at risk of being overshadowed or appropriated by external influences. This paper investigates the efforts to preserve and protect indigenous art traditions, such as batik, wayang, and traditional crafts, amidst the forces of cultural homogenization. It explores the role of the government, non-governmental organizations, and indigenous communities in safeguarding these practices while balancing the demands of modernization and tourism. By examining the complexities surrounding intellectual property rights, cultural appropriation, and the commercialization of indigenous art, the study discusses the challenges of achieving cultural justice for indigenous artists and communities in a globalized society.